Microencapsulated chitosan–dextran sulfate nanoparticles for controled delivery of bioactive molecules and cells in bone regeneration - Valente, Joana (2018)
This research work aimed to synthesize and characterize a novel dual delivery system comprised of BSA-loaded in chitosan–dextran sulfate nanoparticulated carriers and mesenchymal stem cells that are encapsulated into alginate microparticles. The physicochemical and biological characteristics of this novel system, such as, morphology, release, swelling, and cytotoxicity were thoroughly characterized. The results obtained from confocal microscopy demonstrate that chitosan–dextran sulfate nanoparticles and cells are fully encapsulated within alginate microparticles, and spatially dispersed in the microparticle matrix. Moreover, scanning electron microscopy images revealed that these micro-sized carriers possess a rough surface, an important parameter that also promoted proper cell migration and adhesion. Notably, the incorporation of BSA in this duplex nano-micro delivery system extended its release profile throughout time, in comparison with microparticles alone, whilst not eliciting any cell damage. Taken together, these findings suggest that this dual carrier is a versatile delivery system with potential for a spatiotemporally controlled release of bioactive molecules and cells.